2021
DOI: 10.1111/cas.15131
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‐related gene signature associates with immunity and predicts prognosis accurately in patients with osteosarcoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 52 publications
1
65
1
Order By: Relevance
“…In conclusion, these results indicated the important role of RMWs in OS. Although previous studies revealed several prognostic models (including ferroptosis-related gene signatures and autophagy-related prognosis models) for OS [ 27 30 ], this is the first study of the RWM-related prognosis model and RMP patterns for OS. Moreover, the ROC of the RMW model was considerably increased compared with that of the ferroptosis-related gene signature (ROC = 8.06) and autophagy-related prognosis model (ROC = 8.38).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, these results indicated the important role of RMWs in OS. Although previous studies revealed several prognostic models (including ferroptosis-related gene signatures and autophagy-related prognosis models) for OS [ 27 30 ], this is the first study of the RWM-related prognosis model and RMP patterns for OS. Moreover, the ROC of the RMW model was considerably increased compared with that of the ferroptosis-related gene signature (ROC = 8.06) and autophagy-related prognosis model (ROC = 8.38).…”
Section: Discussionmentioning
confidence: 99%
“…Then, GSH and glutathione peroxidase 4 (GPX4) are synthesized in cells. GSH is mainly used as a cofactor in the process of protecting cells from oxidative damage, and GPX4 catalyzes the reduction of lipid peroxide to alcohols [ 26 ]. Therefore, targeting to cancer metabolism is ongoing to develop new therapies for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although individualized treatment for CRC keeps improving, morbidity and mortality of CRC still remain high ( Dekker et al, 2019 ). Recently, many studies have explored the role of cell death modes in oncogenesis and development of CRC, including necroptosis, autophagy and ferroptosis, expecting to find a novel anti-cancer approach for CRC ( Gong et al, 2019 ; Lei et al, 2021 ; Wang et al, 2021 ). Necroptosis, as a non-Caspase-dependent programmed cell death with necrosis characteristics, has attracted extensive attention in the study of multiple cancers ( Gong et al, 2019 ; Ando et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%